Halal Certification of Agricultural Export Commodities: Opportunities and Challenges - Budiyoko Budiyoko; Malinda Aptika Rachmah; Wahyu Adhi Saputro; Dewanti Risa Utami; Kunandar Prasetyo (Universitas Airlangga, 2022)
The fast growth in the number of muslims worldwide made the halal lifestyle a growing trend. This phenomenon has led to high demand for halal products, especially agricultural commodities. Halal certification efforts for agriculture commodities were not only considered beneficial for consumers but also for producers and business actors. With halal certification, consumer confidence in producers and business actors will increase, and it will have a positive impact on the profits of producers and business actors. This study aims to provide an overview of the importance of halal certification efforts for Indonesia's agricultural export commodities so that it can become a reference for the government in developing the national agro-industry. The method used in this research is descriptive analysis with a review of relevant literature through sources from journals, books, proceedings, publications, and electronic media. The results of the literature review show that the biggest challenge to halal certification in Indonesia lies in the procedures and processes. There was a risk of uncleanness occurring at several stages which may allow contamination of unclean and unclean materials during distribution or transportation. Amid during in the fast development of the global halal market, the high potential for the development of halal-certified organic products in Indonesia opens up opportunities for halal certification for agricultural commodities.